COVID-19 and gender: Potential pathways of impact and research challenges - Bryan, Elizabeth; Alvi, Muzna; Ringler, Claudia; Meinzen-Dick, Ruth S. (United States Agency for International Development, 2020)
The impacts of COVID-19 are being felt widely across the globe as most countries and localities urge residents to remain home to slow transmission of the disease. This global health crisis is particularly threatening to the global poor, who may be more susceptible to contracting the virus, have limited access to healthcare, and are more vulnerable to economic impacts. Yet, poor male and female farmers in developing countries may not experience this crisis in the same way. In order to understand how the pandemic is differently affecting men and women in developing countries, IFPRI is implementing a series of phone surveys with poor rural men and women in selected Feed-the-Future countries as part of the Gender, Climate Change, and Nutrition Integration Initiative (GCAN). The same survey is being carried out in India with the grassroots women’s organization, SEWA, as part of the BMZ-supported project on Reaching Smallholder Women with Information Services and Resilience Strategies to Respond to Climate Change.